Konsep Kepentingan Umum Dalam Asas Oportunitas Pada Sistem Peradilan Pidana Indonesia - Hasrina, Sri; Karim, Said; Mirzana, Hijrah Adiyanti (Indonesian Journal of Criminal Law, 2021)
The objective of this research was aimed to analyze the concept of public interest in the principle of opportunity in Indonesian criminal justice system. This research applied normative research method through a statutory approach. The researcher analyzed data by taking inventory of regulatory provisions related to research and carried out qualitative descriptive analysis by describing data and facts resulting from research results with an interpretation, evaluation, and general knowledge. The result of the research indicated that the public interest in the principle of opportunity in the explanation of Article 35 Letter C of Ordinance Number 16 of 2004 concerning the Judiciary of the Republic of Indonesia is the interest of the nation and state and/or the wider community. Nevertheless, it has not provided concrete certainty that can lead to different interpretations.